2002
DOI: 10.1007/s125-002-8247-2
|View full text |Cite
|
Sign up to set email alerts
|

Succesful transplantation of human islets in recipients bearing a kidney graft

Abstract: Refinements in procedures of pancreas enzymatic digestion, and new immunosuppression strategies have allowed clinical trials of islet transplantation in patients with Type I (insulin-dependent) diabetes mellitus [1]. Until recently, the majority of transplants were done in patients who also receive kidney allografts [2]. Clinical results in these patients have not been satisfactory, with a 12 month survival of islet allografts (as defined by basal C-peptide > 0.17 nmol/l) being achieved in less than 40 % of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
37
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 20 publications
1
37
0
2
Order By: Relevance
“…Islet quality tests were performed on material processed shortly before transplant. Preparations were considered adequate for transplantation according to the following criteria: (1) NE (>5,000 per kg bodyweight); (2) purity >20% (dithizone-staining determination of islet/total mass); and (3) islet sterility [16]. Purification was defined to be 20% or greater, because in our experience this limit maintains the tissue volume for transplant to less than 10 ml.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…Islet quality tests were performed on material processed shortly before transplant. Preparations were considered adequate for transplantation according to the following criteria: (1) NE (>5,000 per kg bodyweight); (2) purity >20% (dithizone-staining determination of islet/total mass); and (3) islet sterility [16]. Purification was defined to be 20% or greater, because in our experience this limit maintains the tissue volume for transplant to less than 10 ml.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…Considering that the true expectation of recipients of islet transplantation is independence from exogenous insulin administration, the transplant outcome has often been quantified through reaching insulin independence (1,2,17,18) or, when this is impossible, through the decrease of insulin requirement as percentage of initial need or reduction of absolute values of insulin units (12,19). However, this parameter too may not adequately represent the transplanted ␤-cell mass, especially the in case of multiple infusions, where it is necessary to discriminate the effects of various preparations.…”
mentioning
confidence: 99%
“…Indeed, data in this regard are contrasting and inconclusive (3,26,27), even though the first step of insulin response to an arginine test or the first and the second step to a test for intravenous charge of glucose have been described to correlate with the functioning ␤-cell mass in several studies (17,19,28,29). In particular, the first phase and the area under the curve for insulin in response to intravenous glucose administration were closely related to glycemic control (29), but inversely correlated with the posttransplant insulin requirement and proinsulin levels (17), thus representing a useful test for islet graft function follow-up.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported a high rate of insulin independence and normalization of blood glucose and A1C levels after either pancreas or islet transplantation (3)(4)(5)(6)(7). In patients with type 1 diabetes, pancreas or islet transplantation has improved kidney graft survival (8,9), whereas the positive impact of pancreas transplantation on the native kidney has been counterbalanced by the nephrotoxicity of immunosuppressants, namely calcineurin inhibitors (10,11).…”
mentioning
confidence: 99%